10 year follow-up of randomized trial of laparoscopic Nissen versus Thal fundoplication in children - Skerritt, Clare; Kwok, Chun-Sui; Kubiak, Rainer; Rees, Clare M.; Grant, Hugh W. (Journal of laparoendoscopic & advanced surgical techniques, 2022)
Introduction: The aim of this study was to compare the long-term outcomes of laparoscopic complete (Nissen) fundoplication (LNF) with laparoscopic partial (Thal) fundoplication (LTF) in children. This is the only prospective, randomized study to follow patients up for more than 10 years. Interim results published in 2011 at median 2.5 year follow-up showed that LNF had a significantly lower failure rate compared with LTF. - Materials and Methods: A randomized, controlled trial of LNF versus LTF in children (<16 years) was performed. The primary outcome measure was “absolute” failure of the fundoplication—recurrence of symptoms that merited either reoperation or insertion of transgastric jejunostomy (GJ). Secondary outcomes were “relative” failure (need for postop antireflux medication), complications (e.g., dysphagia), and death. - Results: One hundred seventy-five patients were recruited; 89 underwent LNF, and 86 underwent LTF. Eight patients had no follow-up recorded. At long-term follow-up, 59 patients had died (35%); LNF 37/85 (43.5%) and LTF 22/82 (26.8%), P = .02. Median length of follow-up in survivors was 132 months. There was no statistically significant difference in “absolute” failure rate between LNF 8/85(9.4%) and LTF 15/82 (18%), P = .14. There was no difference in “relative” failure between LNF 7/85 (8.2%) and LTF 12/82 (14%), P = .23. Long-term dysphagia affected 5 out of 108 (4.6%) patients; 3/48 (6.2%) of LNF and 2/60 (3.3%) of LTF (P = .65). - Conclusions: There was no statistically significant difference in ‘absolute’ failure between LNF and LTF at long-term follow-up. Neurologically impaired children have a high mortality rate following fundoplication due to comorbidities. - This trial commenced in 1998 and was approved by the Oxfordshire Research Ethics Committee (No. 04.OXA.18-1998).
Gesehen am 29.07.2024